(untitled) (Research, Society and Development, 2022)
Objective: to characterize the sociodemographic profile of elderly people with diabetes and/or hypertension and to verify the association between sociodemographic characteristics and perceived social support. Methodology: Cross-sectional study, involving 371 elderly people, aged 60 years and over, diagnosed with Diabetes Mellitus and/or Arterial Hypertension and monitored in basic health units in Campina Grande-PB. The analyzed variables were selected from the sociodemographic questionnaire and Social Support Inventory. Multiple linear regression analysis was performed to verify how sociodemographic variables impacted levels of perceived social support. Results: There are significant associations between perceived social support and marital status (c2(3) = 10.954, p <0.012, V = 0.173); religion (c2(3) = 10.764, p < 0.013, V = 0.172) and income (c2(3) = 9.216, p < 0.027, V = 0.159). Evidencing that married elderly were 0.19 times more likely to perceive high social support compared to single elderly. Conclusion: Social support is essential to deal with personal and interpersonal issues during aging, which points to the need to offer actions, in the context of primary health care, focused on health promotion, in order to provide a perspective on social support networks for the elderly, particularly in the context studied, which contribute to the realization of health care based on the notion of expanded health.